2009
DOI: 10.1111/j.1600-0587.2009.05823.x
|View full text |Cite
|
Sign up to set email alerts
|

Species richness of crustacean zooplankton and trophic structure of brackish lagoons in contrasting climate zones: north temperate Denmark and Mediterranean Catalonia (Spain)

Abstract: We sought to identify environmental factors influencing crustacean zooplankton species richness in brackish lagoons and to elucidate whether crustacean zooplankton species richness and trophic structure of brackish lagoons differ among two regions with contrasting temperatures. We sampled 35 and 42 brackish lagoons (salinity ranging from 0.3 to 55) in Mediterranean Catalonia (NE Spain) and northern-temperate Denmark, respectively. No significant differences were found in total crustacean zooplankton species ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
81
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(101 citation statements)
references
References 56 publications
12
81
2
2
Order By: Relevance
“…from freshwater to brackish levels) its effects may in some cases override all other environmental and pressure factors such as temperature or eutrophication, as shown for zooplankton (Brucet et al, 2009). This is supported by recent studies of streams in the USA where conductivity proved to be one of the most important stressors associated with biological degradation (Vander Laan et al, 2013).…”
Section: Effects Of Changes In Salinity/conductivitysupporting
confidence: 59%
See 2 more Smart Citations
“…from freshwater to brackish levels) its effects may in some cases override all other environmental and pressure factors such as temperature or eutrophication, as shown for zooplankton (Brucet et al, 2009). This is supported by recent studies of streams in the USA where conductivity proved to be one of the most important stressors associated with biological degradation (Vander Laan et al, 2013).…”
Section: Effects Of Changes In Salinity/conductivitysupporting
confidence: 59%
“…In addition, elevated salinity can reduce the zooplankton growth rate due to osmotic stress in salt-sensitive taxa (Table S3). Similarly, in Spain and France, salinity appears to be the main environmental factor structuring the zooplankton and invertebrate communities in lakes and ponds (Green et al, 2005;Boix et al, 2008;Waterkeyn et al, 2008;Brucet et al, 2009). Not only Mediterranean regions suffer from increased salinity due to climate change.…”
Section: Effects Of Changes In Salinity/conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Derry et al (2003) found that in Canadian shallow lakes with chloride waters, B. plicatilis and the hapacticoid copepod Cletocampus sp., were the dominant species. However, it cannot be claimed that some abundant species such as Moina micrura and Metacyclops mendocinus should be considered indicators of a narrow range of salinity or a limited ionic concentration because they generally show a relatively wide range of tolerance (Rzóska, 1961;Alonso, 1996;Sterza and Fernández, 2006;Santangelo et al, 2008;Brucet et al, 2009).…”
Section: Zooplankton Featuresmentioning
confidence: 99%
“…Apart from Northeastern Europe (e.g. Kernan et al, 2009) it was mentioned in Poland (Kuczynska-Kippen, 2006;Adamczuk, 2009), Germany (Nauwerck, 1991;Hofmann, 1996;Straile & Müller, 2010), Denmark (Brucet et al, 2009), Belgium (Malbrouck et al, 2005) and in Northern Italy (Margaritora, 1983). In the Iberian Peninsula B.…”
mentioning
confidence: 99%